Pengelolaan Keuangan Laba Rugi pada Home Industry Alat Musik UD Kayu Mas Balung, Jember - Puspitaningtyas, Erlinda; Toha, Akhmad; Prakoso, Aryo (e-Sospol, 2017)
Abstract Finance management is aimed at finding out the finance position of a company so as to reveal finance condition, which serves as the cornerstone in business decision making. Finance management also functions as an evaluation tool to business appropriateness in order to assess its accountability, probe its finance condition related to profit and loss, control business finance, and meet the obligation as citizen to pay tax. The finance condition aforementioned is germane to the administration of profit-and-loss finance which complies with the procedure as well as standard stipulated in Law number 20 of 2008, concerned with the obligation of home industry to carry out finance management as regulated in The Finance Standard of Entity with no Public Accountability (commonly known as SAK ETAP) to put home industry at ease when dealing with finance management. This research was projected to explain profit-and-loss finance management at UD Kayu Mas Balung, a home industry specializing on music instrument, in Jember district. The research employed qualitative method, coupled with descriptive analysis. The research findings revealed the profit-and-loss finance management which already complied with the very standard due to improvement on several production processes and the documents of finance administration carried out by the business owner.